Template JCEC - Editorial Team/Equipe Editorial JCEC (The Journal of Engineering and Exact Sciences)
Open-Access ISSN 25271075 The Journal of Engineering and Exact Sciences - JCEC is an international journal for scientists, engineers, technologists, which publishes original scientific and professional papers, review articles and surveys. The focuses and scope include, but are not limited to: 1) Biotechnological Processes; 2) Engineering and Food Technology; 3) Transport Phenomena; 4) Environmental Engineering and Clean Technologies; 5) Engineering of Chemical Reaction and Catalysis; 6) Simulation, Optimization and Process Control; 7) Engineering Materials and Nanotechnology; 8) Engineering of Separations and Thermodynamics; 9) Engineering Education and Science Education; 10) Chemistry; 11) Extension Project in Engineering and related areas; 12) Mechanical Engineering; 13) Industrial Engineering; 14) Innovation Lecture Notes; 15) Energy and 16) Special Topics.